(untitled) (American Journal of Islam and Society, 2003)
Prior to the landmark Supreme Court decision of June 1963, which banned public prayer from the public schools, Christian religious education was often a routine part of the overt instruction provided by the American public school system. However, in the wake of that legal milestone, even though instruction in the Judeo-Christian interpretation of religious history continued to be taught covertly, American churches began relying more heavily on providing Christian religious education. This article briefly presents Christianity’s contemporary status in the United States and reviews such religious education methods as Sunday school, vacation Bible school, Christian youth groups, catechism, private Christian schools, Youth Sunday, and children’s sermons. The survey concludes with a look at the growing interface between such education and the lessons of psychology as well as training and certifying Christian religious educators.